2020
DOI: 10.1111/jan.14702
|View full text |Cite
|
Sign up to set email alerts
|

Care dependency and management of urinary incontinence in nursing homes: A descriptive study

Abstract: Aim To explore the differences in managing urinary incontinence in residents in nursing homes aged 65 years or older in relation to their care dependency. Design The 2015 data of the Dutch annual independent (Inter)national Prevalence Measurement of Quality of Care of Maastricht University were used. The design involved a cross‐sectional, multi‐centre point prevalence measurement in hospitals, care homes, and home care. Methods Secondary data analysis on the data provided by care home organizations. Results In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…7 Furthermore, Huion et al observed significant differences between dependent and independent older adults regarding UI. 5 Dependent individuals lost a large amount of urine daily, while independent individuals lost tiny amounts, such as drops and splashes, 3 to 4 times a month.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Furthermore, Huion et al observed significant differences between dependent and independent older adults regarding UI. 5 Dependent individuals lost a large amount of urine daily, while independent individuals lost tiny amounts, such as drops and splashes, 3 to 4 times a month.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Abrams et al 4 describe involuntary loss of urine as a manifestation triggered by morphological changes in the bladder observed with aging, such as decreases in bladder elasticity and ureteric jet velocity, leading to uninhibited detrusor contractions. [4][5][6] In addition, pelvic floor disorders may cause incontinence, such as contractile dysfunction and involuntary reflexes of the external anal sphincter. 6 UI has multiple predisposing factors and outcomes, meaning that interventions in this condition demand adequate assessment, planning, and multifactorial action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing dependency is defined as the amount of care provided by the nurse that can be reflected by the total nursing time spent with the patient. Studies have shown that patients who require high workload from the nursing staff are those with high dependency on care in ICU, emergency and rehabilitation units, and nursing homes (Ferreira et al, 2017; Hatfield et al, 2003; Huion et al, 2021; Varndell et al, 2016). Nursing dependency is a patient classification system (PCS) currently used as an indirect tool for determining care hours according to the complexity and amount of care that a patient requires (Ferreira et al, 2017; Hatfield et al, 2003; Helmer, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The last Consultation of the International Continence Society states that behavioural strategies with or without exercises to improve mobility and toileting result in modest short-term improvements in UI among NH residents [ 6 ]. However, the most frequent management strategy used in the NH setting (and sometimes the only strategy) is the use of absorbent materials [ 1 , 26 ].…”
Section: Introductionmentioning
confidence: 99%